The Relationship between Tourism and Economic Development in the Greater Mekong Sub-Region: Panel Cointegration and Granger Causality - NONTHAPOT, Sakkarin (Journal of Advanced Research in Law and Economics, 2017)
This paper examines the causal relationship between tourism and economic development. Tourism is considered in two ways; number of international tourist arrivals and tourism receipts. The data are collected from the five Greater Mekong Sub-region (GMS) countries i.e. Myanmar, Cambodia, Lao PDR, Thailand and Vietnam; and the Yunnan and Guangxi provinces of China. The sample period is semi annual data from 2000 to 2012 and is also estimated by a panel data approach. This study finds a long-run relationship is unidirectional running from the number of international tourist arrivals to economic development; and from economic development to tourism receipts. The short-run causality is unidirectional running from the international tourist arrivals to economic development only. This study suggests that the GMS countries should concentrate on tourism marketing promotion and expand economic development, especially in tourism investment such as enhancing the tourism and hotel industry to meet international standard for tourism sustainability as an entire region.